Design understanding the principles - Hollaender, Sherry; Roach, John; Strzelinski, James (New York : Insight Media, 2007)
Featuring a professor and students from Parsons School of Design, this program describes how elements of design (color, size, texture, line, and shape) are combined to achieve design principles such as unity, dominance, contrast, and rhythm. Examples from fields such as architecture, fashion, interior design, theater, product design, and printed publications are included
Title from title screen
DVD format
Keywords: Design